Social Structure and Epistemic Privilege: Reconstructing Lukács’s Standpoint Theory - Stahl, Titus (Análisis. Revista de investigación filosófica, 2023)
Lukács is widely recognized as being the first critical theorist to have explicitly developed the idea of a “standpoint theory”. According to such a theory, members of oppressed groups enjoy an epistemic privilege regarding the nature of their oppression. However, there is no agreement regarding what precise argument Lukács offers for his claims regarding the alleged epistemic privilege of the working class. Additionally, it remains unclear whether later feminist standpoint theories share any continuity with Lukács’s argument. In this analysis, I identify four arguments for the epistemic privilege of oppressed groups that could be attributed to Lukács. I argue that, although Lukács does not consistently endorse any specific argument, the most promising interpretation suggests that epistemic privilege arises from a contradiction between the norms that guide the self-understanding of such groups and the effects of the social practices they are socially obligated to engage in.